THE RELATIONSHIP BETWEEN EXCLUSIVE BREASTFEEDING, SPOUSAL SUPPORT AND MATERNAL NUTRITIONAL STATUS WITH BREAST MILK PRODUCTION AMONG BREASTFEEDING MOTHERS AT THE SITI SRI KOMALASARI MIDWIFE CLINIC, CIBEREUM VILLAGE, CIANJUR IN 2022 - Alifa Intan Al-Muttahasin; Agus Santi Br. Ginting; Agustina S (Universitas Dharmawangsa Medan, 2026)
Breast milk is an ideal source of nutrition and the safest food for babies during the first 4-6 months of life. Reduced breast milk production is a problem in new mothers and there are factors that affect breast milk production such as support from the husband, closest people, and nutritional adequacy of the mother and exclusive breastfeeding. The purpose of this study was to determine the relationship between exclusive breastfeeding, husband support, and maternal nutritional adequacy with breast milk production in breastfeeding mothers at PMB Midwife Siti Dri Komalasari KP. Cibereum Cianjur. This research is a quantitative type that is analytical in nature with a cross sectional approach. This research was conducted at PMB Midwife Siti Sri Komalasari KP. Cibereum Cianjur. The research time is June-August 2022. In this study, the population was 40 breastfeeding mothers and the sample used saturated samples in which the entire population was sampled. Researchers used the Chi Square test. Based on the results of the study Frequency distribution, it is known that the majority of breastfeeding mothers in PMB Midwife Siti Sri Komalasari KP. Cibereum Cianjur of 25 respondents (62.5%) had a lot of breast milk production and 15 respondents (37.5%) had little breast milk production. The results of the exclusive breast milk statistical test with the production of breast milk for breastfeeding mothers with a value of P value = 0.026, husband support with breast milk production of breastfeeding mothers with a value of P value = 0.000, Nutritional adequacy with the production of breast milk for breastfeeding mothers with a value of P value = 0.009. In conclusion, there is a relationship between exclusive breastfeeding, husband support, maternal nutritional adequacy and the production of breast milk for mothers in the pmb midwife Siti Sri Komalasari KP. Cibereum Cianjur. Advice for PMB Midwife Siti Sri Komalasari is expected to increase socialization to the community, especially breastfeeding mothers about exclusive breastfeeding, nutritional adequacy, and breast milk production.